Ecological status of sea cucumber resources across depth strata in Kapadiri Village, Raja Ampat, Southwest Papua, Indonesia - NENENG SUARNO KALIDI; SALIYADI SALIYADI; ELLEN LOUPATTY; GULAM ARAFAT; NEVI AITEM (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Kalidi NS, Saliyadi, Loupatty E, Arafat G, Aitem N. 2025. Ecological status of sea cucumber resources across depth strata in Kapadiri Village, Raja Ampat, Southwest Papua, Indonesia. Biodiversitas 26: 6502-6512. This study presents the first quantitative ecological assessment of sea cucumber (Holothuroidea) populations in the waters of Kapadiri Village, Raja Ampat, Indonesia, a coastal area subjected to long-term harvesting without formal management regulations. The study aimed to analyze species composition, community structure, and population density across two depth strata in order to characterize the current ecological condition of sea cucumber resources. Field surveys were conducted at five stations representing seagrass, coral reef, and sandy habitats at depths of <5 m and >5 m. Quadrat transects (60 m²) were applied in shallow areas, while belt transects (200 m²) were used in deeper zones. Nine sea cucumber species were recorded, with Holothuria edulis, H. atra, and H. scabra being the most abundant. Population densities ranged from 0.083-0.167 ind/m² in shallow waters and 0.105-0.230 ind/m² at depths >5 m. Community indices indicated moderate diversity, high evenness, and low dominance, reflecting a relatively balanced community at low overall abundance. A quasi-Poisson generalized linear model showed that depth and station significantly influenced density variation, whereas their interaction was not significant, indicating a consistent depth-related pattern across stations. Measured environmental parameters (temperature, salinity, pH, and dissolved oxygen) were within tolerance ranges reported for tropical sea cucumbers, suggesting that habitat conditions remain environmentally suitable. However, the consistently low population densities observed across all stations indicate that sea cucumber stocks are likely under pressure, inferred from density patterns and comparisons with regional studies. These findings underscore the need for strengthened community-based management, including adaptive harvesting regulations and targeted habitat protection, to support the recovery and long-term sustainability of sea cucumber populations in Kapadiri Waters.